THE LIBYAN REVOLUTION OF 2011 AND THE IMPACT OF MUAMMAR GADDAFI'S IMPEACHMENT ON LIBYA AND OTHER ARAB COUNTRIES - Shohib, Muh Ilham; Baidhowi, M. Kholil; Amrosi, Amrosi (At-Turost : Journal of Islamic Studies, 2023)
One of the leaders who once led the Libyan state was Muammar Gaddafi and his leadership period made him the longest-serving leader in Libyan history. However, in his 42nd year as leader in Libya, Muammar Gaddafi was impeached from office. This was none other than due to several factors, including the Libyan people being intervened by foreigners who had the aim of controlling Libya's abundant oil, the economic crisis where the natural wealth from the oil could only be enjoyed by Muammar Gaddafi and his family, the impact of the Arab Spring who have successfully impeached two other leaders, namely Ben Ali in Tunisia and Mubarok in Egypt, there is a motive for revenge from supporters of King Idris who was in a coup by Muammar Gaddafi. Several of these factors made the Libyan people increasingly eager to impeach the former colonel, Muaamar Gaddafi. Every event must have an impact, and the impact of the impeachment of Muammar Gaddafi must be borne by Libya itself and has an impact on the psychology of the people and leaders in other countries that have the same government system and their people have the same destiny. The impeachment could result in Libya becoming a puppet of the foreigners who took part in impeaching it. Keywords: Revolution, factors, and the impact of the impeachment of Muammar Gaddafi